One day ebook - Nicholls, David (2010)
NOW A NETFLIX SERIES  • NEW YORK TIMES BESTSELLER • TWO PEOPLE. ONE DAY. TWENTY YEARS. • What starts as a fleeting connection between two strangers soon becomes a deep bond that spans decades. •  "[An] instant classic. . . . One of the most ...emotionally riveting love stories you’ll ever encounter." — People   It’s 1988 and Dexter Mayhew and Emma Morley have only just met. But after only one day together, they cannot stop thinking about one another. Over twenty years, snapshots of that relationship are revealed on the same day—July 15th—of each year. They face squabbles and fights, hopes and missed opportunities, laughter and tears. Dex and Em must come to grips with the nature of love and life itself. As the years go by,  the true meaning of this one crucial day is revealed.    "[A] surprisingly deep romance...so thoroughly satisfying." — Entertainment Weekly